2010
DOI: 10.1128/jvi.02725-09
|View full text |Cite
|
Sign up to set email alerts
|

Numerous Conserved and Divergent MicroRNAs Expressed by Herpes Simplex Viruses 1 and 2

Abstract: Certain viruses use microRNAs (miRNAs) to regulate the expression of their own genes, host genes, or both. Previous studies have identified a limited number of miRNAs expressed by herpes simplex viruses 1 and 2 (HSV-1 and -2), some of which are conserved between these two viruses. To more comprehensively analyze the miRNAs expressed by HSV-1 or HSV-2 during productive and latent infection, we applied a massively parallel sequencing approach. We were able to identify 16 and 17 miRNAs expressed by HSV-1 and HSV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
200
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(210 citation statements)
references
References 68 publications
9
200
1
Order By: Relevance
“…2A). Sequences deriving from in or around the OriLyt of both rat and mouse cytomegaloviruses (RCMV and MCMV, respectively), as well as some other herpesviruses, such as herpes simplex virus 1 (HSV-1) and HSV-2, have previously been reported to encode miRNAs or postulated to act as RNA primers for the replication of the viral genome (8,17,30,35).…”
Section: Resultsmentioning
confidence: 99%
“…2A). Sequences deriving from in or around the OriLyt of both rat and mouse cytomegaloviruses (RCMV and MCMV, respectively), as well as some other herpesviruses, such as herpes simplex virus 1 (HSV-1) and HSV-2, have previously been reported to encode miRNAs or postulated to act as RNA primers for the replication of the viral genome (8,17,30,35).…”
Section: Resultsmentioning
confidence: 99%
“…HSV-1 encodes 16 miRNA identified by deep-sequencing studies of virus-infected cells; 11 of these miRNAs are encoded within or near to the LAT gene (Jurak et al, 2010) with seven detected in latently infected mouse or human ganglia (Umbach et al, 2009;Held et al, 2011; Kramer et al, 2011). Three HSV-1 miRNAs are antisense to, and reduce expression of, virus genes involved in the initiation of virus gene transcription (ICP4), neurovirulence (ICP34.5) and inactivation of host antiviral pathways (ICP0/RL2) (Umbach et al, 2008; Flores et al, 2013).…”
Section: During Latency Hsv-1 and Vzv Gene Transcription Is Restrictedmentioning
confidence: 99%
“…Specifically, promoters for HSV-1 genes expressed during lytic infection (ICP4, ICP27 and ICP8) are associated with H3K9 and H3K27 trimethylations in ganglia of latently infected mice, and these post-translational modifications indicative of facultative heterochromatin are reduced when latency is established with HSV-1 containing mutations precluding LAT transcription (Amelio et al, 2006a;Cliffe et al, 2009; Kwiatkowski et al, 2009). Interestingly, LAT-dependent heterochromatin formation (H3K27me 3 ) on lytic virus promoters during establishment of latency -a phenomenon that is virus strain and infection model-specific -may involve modifications of host polycomb repressor complex group 2 protein (PRC-2) as Suz12, a normal PRC-2 component, is not detected on latent HSV-1 DNA during silencing of the virus genome (Kwiatkowski et al, 2009;Cliffe et al, 2013).HSV-1 encodes 16 miRNA identified by deep-sequencing studies of virus-infected cells; 11 of these miRNAs are encoded within or near to the LAT gene (Jurak et al, 2010) with seven detected in latently infected mouse or human ganglia (Umbach et al, 2009;Held et al, 2011; Kramer et al, 2011). Three HSV-1 miRNAs are antisense to, and reduce expression of, virus genes involved in the initiation of virus gene transcription (ICP4), neurovirulence (ICP34.5) and inactivation of host antiviral pathways (ICP0/RL2) (Umbach et al, 2008; Flores et al, 2013).…”
mentioning
confidence: 99%
“…Specifically HSV-1 and HSV-2 have been reported to express at least 27 miRNAs (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Analyses of 17 of these miRNAs have shown that they differ in their requirements for synthesis in productively infected cells.…”
mentioning
confidence: 99%